Direito à cidade e participação social: uma análise do processo participativo do plano diretor da cidade de Guarulhos - SP (2011-2019) - Santos, Rodrigo Souza (2022)
This dissertation aims to analyze the right to participatory democracy, constitutionally guaranteed in the Magna Carta of 1988 and imposed the federal statute - federal law nº 10.257/2019, for this purpose, we will try to carry out a synthesis of the scenario of social participation wich must be used in the preparation and reviewing of the Municipal Master Plan, conceptualizing the theoretical-referential bases this planing instrument and application, as well as examining how democracy participation, wich is guaranteed constitutional right also imposed as mandatory condition in Master Planed, has gained a significant and strong evidence in urban lives. Finally, we will analyze the level of power that citizens had in the revision of the Participatory Master Plan of Guarulhos – SP based on the formulation developed by Arnstein (2002) and by Souza, as well as analyzing some of the urban instruments of territorial ordering agreed in the Guarulhos Municipal Master Plan, promoting social function of property and a fair cities for all.